The Effect of Artificial Intelligence on Sustainable Entrepreneurial Ecosystems: Evidence from Lima, Peru - Olórtegui Alcalde, Luis Miguel; Saldaña Narro, Julio Brayan; Gasparrini Cañas, Víctor Gerardo; Marcelo Quispe, Luis Alberto (LACCEI, 2025)
The research examines the impact of artificial intelligence (AI) on sustainable entrepreneurial ecosystems in Lima, Peru, highlighting its influence on business sustainability and competitiveness. Utilizing a quantitative approach based on structural equation modeling (PLS-SEM) and a non-experimental design, the study analyzed data from 385 entrepreneurs with experience in and use of advanced technologies. The findings reveal that AI significantly enhances business sustainability (β=0.63, p